TIME COURSE OF BODY WEIGHT REDUCTION IN ELDERLY OVERWEIGHT OUTPATIENTS MOTIVATED THROUGH EMPATHETIC REINFORCEMENT. (June 2018) - Marotta, T.; De Mitri, A.
Abstract : Objective: It is known that compliance to diet regimens weakens during time. Improving patient motivation through empathetic reinforcement could help to overcome this problem. The effects of recommendations about this issue included in the US high blood pressure guidelines have been studied in elderly overweight patients, attending two public Internal Medicine facilities conducted by the same physician. Design and method: Overweight patients over 60 years of age followed-up at least 5 times after baseline were included in the study. Diet and, if indicated, pharmacological treatment were prescribed at baseline and changed when necessary. Patients' issues about treatment directions were discussed at each visit. Body weight and blood pressure (BP) data at baseline and at the first 5 follow-up visits are presented. Results: 95 patients (75 F, age at baseline = 65 ± 6 years) were studied. 81 of them (85%) were hypertensive. Mean follow-up duration was 143 weeks (24 to 669, median = 65). Body mass index (BMI) was significantly reduced during follow-up (33.7 ± 5 to 31.7 ± 5 kg/m 2, p < 0.001), such as waist circumference (108 ± 10 to 103 ± 8 cm, p < 0.001), and BP (151/84 ± 26/13 to 136/77 ± 21/11 mmHg, p < 0.001). A progressive BMI reduction was obtained, without evidence of reversal along time (p < 0.001 at the general linear model for repeated measures, see plot). BP decreased until a plateau at the 4th follow-up visit, with mean values below 140/90 mmHg since the 2nd follow-up visit. Changes in BMI and BP along time were not significantly affected by either sex or education level. Season at which visits were performed did not affect BMI, whilst significantly lower BP levels were observed in summer in comparison to winter (135/80 ± 21/12 vs 144/82 ± 20/12 mmHg, p < 0.005 at ANOVA), but not in comparison to spring and autumn. When considered as a covariate, season of the visit independently contributed to BP level, together with progression of follow-up (p < 0.005). Figure. No caption available. Conclusions: These data strongly suggest that implementing the current recommendations on motivational reinforcement improves adherence to therapy and contributes to avoid reversal of treatment effect during time. Season of the year can affect BP control, but does not interfere with the effects of hypocaloric diet on BW.